THE DYNAMICS OF BERTRAND PRICE COMPETITION WITH COST‐REDUCING INVESTMENTS. (27th August 2018) - Iskhakov, Fedor; Rust, John; Schjerning, Bertel
Abstract: We extend the classic Bertrand duopoly model of price competition to a dynamic setting where competing duopolists invest in a stochastically improving production technology to "leapfrog" their rival and attain temporary low‐cost leadership. We find a huge multiplicity of Markov‐perfect equilibria (MPE) and show that when firms move simultaneously the set of all MPE payoffs is a triangle that includes monopoly payoffs and a symmetric zero mixed strategy payoff. When firms move asynchronously, the set of MPE payoffs is strictly within this triangle, but there still is a vast multiplicity of MPE, most of which involve leapfrogging.